Morphology of human sinoatrial node and its surrounding right atrial muscle in the global obesity pandemic—does fat matter? - Chen, Weixuan; Rams, Daniel; Zając, Maciej; Albalawi, Raghad; Atkinson, Andrew J.; Aminu, Abimbola J.; Mazur, Malgorzata; Hołda, Mateusz K.; Walocha, Jerzy; Gil, Krzysztof; Kuniewicz, Marcin; Dobrzynski, Halina (Frontiers in Medicine, 2024)
Compared to the surrounding RA, the SN in all four groups has significantly more connective tissue (P≤0.05) (young non-obese individuals, aged non-obese individuals, aged obese individuals and young obese individuals) and significantly smaller nodal cells (P≤0.05) (young non-obese individuals, aged non-obese individuals, aged obese individuals, young obese individuals). In ageing, overall, there was a significant increase in fibrosis, apoptosis, and cellular hypertrophy in the SN (P≤0.05) and RA (P≤0.05). Obesity did not further exacerbate fibrosis but caused a further increase in cellular hypertrophy (SN P≤0.05, RA P≤0.05), especially in young obese individuals. However, there was more infiltrating fat within the SN and RA bundles in obesity. Compared to the young nonobese individuals, the young obese individuals showed decreased P wave amplitude and P wave slope in aVF lead.Ageing and obesity are two risk factors for extensive fibrosis and cellular hypertrophy in SN and RA. Obesity exacerbates the morphological alterations, especially hypertrophy of nodal and atrial myocytes. These morphological alterations might lead to functional alterations and eventually cause cardiovascular diseases, such as SN dysfunction, atrial fibrillation, bradycardia, and heart failure.